Large Deletions and Point Mutations Involving DOCK8 in the Autosomal Recessive Form of the Hyper-IgE Syndrome - Engelhardt, Karin R. (2009)
BACKGROUND: The genetic etiologies of the hyper-IgE syndromes are diverse. Approximately 60-70% of patients with hyper-IgE syndrome have dominant mutations in STAT3, and a single patient was reported to have a homozygous TYK2 mutation. In the remaining hyper-IgE syndrome patients, the genetic etiology has not yet been identified. METHODS: We performed genome-wide single nucleotide polymorphism analysis for nine subjects with autosomal recessive hyper-IgE syndrome to locate copy number variations and homozygous haplotypes. Homozygosity mapping was performed with twelve subjects from seven additional families. The candidate gene was analyzed by genomic and cDNA sequencing to identify causative alleles in a total of 27 patients with autosomal recessive hyper-IgE syndrome. FINDINGS: Subtelomeric microdeletions were identified in six subjects at the terminus of chromosome 9p. In all patients the deleted interval involved DOCK8, encoding a protein implicated in the regulation of the actin cytoskeleton. Sequencing of subjects without large deletions revealed 16 patients from nine unrelated families with distinct homozygous mutations in DOCK8 causing premature termination, frameshift, splice site disruption, single exon- and micro-deletions. DOCK8 deficiency was associated with impaired activation of CD4(+) and CD8(+) T cells. INTERPRETATION: Autosomal recessive mutations in DOCK8 are responsible for many, though not all, cases of autosomal recessive hyper-IgE syndrome. DOCK8 disruption is associated with a phenotype of severe cellular immunodeficiency characterized by susceptibility to viral infections, atopic eczema, defective T cell activation and TH17 cell differentiation; and impaired eosinophil homeostasis and dysregulation of IgE.